1980
DOI: 10.2307/1510429
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy and Severity in the Learning Disabled: A Consolidated Perspective

Abstract: This paper presents a consolidated criteria model which can be used to identify the discrepancy and severity level of learning disabled students. Academic and socialization skills are evaluated in light of seven considerations: 1) the problem's effect on other abilities, 2) academic and socialization problem correspondence, 3) alteration of future life needs, 4) remediation versus compensation, 5) effect on social skills with peers and adults, 6) strengths and weaknesses, and 7) avoidance of problem areas. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Students in this subgroup were found to be consistent with the description of mildly learning disabled proposed by Weller (1980) in her severity model. These students' perfomance deficits did not tend to interfere with their adaptive capabilities, no vast processing discrepancies were observed, and there was poor correspondence between their academic problems and adaptive performance.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Students in this subgroup were found to be consistent with the description of mildly learning disabled proposed by Weller (1980) in her severity model. These students' perfomance deficits did not tend to interfere with their adaptive capabilities, no vast processing discrepancies were observed, and there was poor correspondence between their academic problems and adaptive performance.…”
Section: Discussionsupporting
confidence: 79%
“…The WSSAB incorporated 70 adaptive characteristics of learning disabled individuals in four domains that identified two subtypes of learning disabled individuals by severity: mild-to-moderate and moderateto-severe. The two subgroups, identified by teacher ratings and validated by a criterion of learner profiles (Weller, 1980), indicated that mild-to-moderate learning disabled individuals exhibited adaptive capabilities similar to those of non-handicapped individuals, and moderate-to-severe learning disabled individuals exhibited adaptive behavior significantly different from the non-handicapped. Although functional severity levels were identified, the relationship of adaptive behavior and educational performance was not empirically established.…”
mentioning
confidence: 99%
“…Academically, they tend to possess significant deficits in verbal and nonverbal skills (Boder, 1973) that frequendy result in WISC-R scatter (McKinney, 1984), and academic difficulties that respond poorly to remedial and compensatory education (Weller, 1980). If individuals of this subtype were to be compared to any group that has received research attention, it would probably be the clinical population described by Orton (1937) or Johnson and Myklebust (1967).…”
Section: Global Functional Disorders Subtypementioning
confidence: 99%
“…McConaughty and Ritter (1985) and Lahey, Stempniak, Robinson, and Tyroler (1978) identified profiles that could be interpreted as subtypes on personality and social-emotional variables. Weller and her associates (Weller, 1980;Weller & Strawser, 1981;Well, Strawser, 8c Buchanan, 1985; have incorporated many of these behavioral variables under the rubric of adaptive behavior and identified severity subtypes based on adaptive behavior differences.…”
mentioning
confidence: 99%
“…High correlations between the particular intelligence and achievement tests used, statistical regression, test reliability problems, and standard errors of measurement in either IQ or achievement tests are commonly cited as artifacts which may affect the interpretation that an actual discrepancy exists between a pupil's achievement and his/her potential (Cone & Wilson, 1981;Page, 1980;Reynolds, 1981). Therefore, several formulas, or tables derived from formulas, have recently been suggested to account for the statistical properties of IQ and achievement tests in establishing the presence of a significant discrepancy for purposes of a learning disability diagnosis (Danielson & Bauer, 1978;Elliott, 1981;McLeod, 1979;Salvia & Clark, 1973;Shephard, 1980;Weller, 1980). One such formula was at one point proposed as an integral part of the learning disability definition under Public Law 94-142 (Senf, 1978).…”
mentioning
confidence: 99%